The Desert Grassland - Van Devender, Thomas R.; McClaran, Mitchel P., 1956-; Project Muse. (Tucson : University of Arizona Press, 1995)
The mixed grass and shrub vegetation known to scientists as desert grassland is common to the basins and valleys that skirt the mountain ranges throughout southwestern North America, extending from Arizona, New Mexico, and Texas down through thirteen Mexican states. Leading experts in geography, biology, botany, zoology, and geoscience present new research on the desert grassland and review a vast amount of earlier work. They reveal that present-day grasses once grew in the ice age forests that existed in these areas before the climate dried and the trees vanished, and how the intensity and frequency of fire can influence the plant and animal species of the grassland. They also document how the influence of humans - from Amerindians to contemporary ranchers, public land managers, and real estate developers - has changed the relative abundance of woody and herbaceous species and how the introduction of new plants and domesticated animals to the area has also affected biodiversity. The book concludes with a review of the attempts, both failed and successful, to reestablish plants in desert grasslands affected by overgrazing, drought, and farm abandonment.
Desert grasslands and grasses / Mitchel P. McClaran -- Desert grassland, mixed shrub savanna, shrub steppe, or semidesert scrub? The dilemma of coexisting growth forms / Tony L. Burgess -- Desert grassland history: changing climates, evolution, biogeography, and community dynamics / Thomas R. Van Devender -- Landscape evolution, soil formation, and Arizona's desert grasslands / Joseph R. McAuliffe -- Role of fire in the desert grasslands / Guy R. McPherson -- Diversity, spatial variability, and functional roles of invertebrates in the desert grassland ecosystems / Walter G. Whitford, Gregory S. Forbes, and Graham I. Kerley -- Diversity, spatial variability, and functional roles of vertebrates in the desert grassland / Robert R. Parmenter and Thomas R. Van Devender -- Human impacts on the grasslands of southeastern Arizona / Conrad J. Bahre -- Revegetaion in the desert grassland / Bruce A. Roundy and Sharon H. Biedenbender.
Description based on print version record.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Grassland ecology -- Mexico; Grassland ecology -- Southwestern States; Desert ecology -- Mexico; Desert ecology -- Southwestern States; Grasslands -- Mexico; Grasslands -- Southwestern States; Deserts -- Mexico; Deserts -- Southwestern States; Ecology; Grasslands; Deserts; Mexico; Southwestern United States; Écologie des prairies -- Mexique; Écologie des prairies -- États-Unis (Sud-Ouest); Écologie des déserts -- Mexique; Écologie des déserts -- États-Unis (Sud-Ouest); Prairies -- Mexique; Prairies -- États-Unis (Sud-Ouest); Déserts -- Mexique; Déserts -- États-Unis (Sud-Ouest); SCIENCE / General; Grasslands; Grassland ecology; Deserts; Desert ecology; United States -- Southwestern States; Mexico; Écologie des prairies -- Mexique; Écologie des prairies -- États-Unis (sud-ouest); Écologie des deserts -- Mexique; Écologie des deserts -- États-Unis (sud-ouest); Prairies -- Mexique; Prairies -- États-Unis (sud-ouest); Deserts -- Mexique; Deserts -- États-Unis.; desert; desert -- herbage -- Etats-Unis -- sud-ouest.; desert -- herbage -- Mexique